Hypertension and childhood migration: a nationwide study of 2.7 million adolescents. Issue 4 (April 2019) - Peled, Alon; Gordon, Barak; Twig, Gilad; Grossman, Ehud; Matani, Doraid; Derazne, Estela; Afek, Arnon
Abstract : Objectives: Immigration studies can shed light on hypertension development and reveal high-risk populations. To this end, we investigated the association between age at immigration and hypertension occurrence at adolescence among immigrants to Israel. Methods: We analyzed cross-sectional data on 2 681 294 adolescents assessed for mandatory military service at approximately 17 years of age between 1967 and 2016. The study population constituted of 410 488 immigrants with origins in Ethiopia, Middle East and North Africa, Former USSR and Western Countries. Age at immigration was categorized into 0–5, 6–11 and 12–19 years. Odds ratios (ORs) for hypertension were calculated according to age at immigration with Israel-born participants as controls. Models were made to account for possible confounders. Additionally, the study population was stratified by country of origin and each immigrant group referenced to Israel-born participants of the same origin. Results: In the fully-adjusted model, immigrants arriving until age 11 years had comparable ORs for hypertension to the Israeli-born reference group, whereas recent immigrants, arriving at age 12–19 years had a marked lower OR of 0.30 (95% CI 0.27–0.33; P < 0.001). The lower hypertension odds among recent immigrants persisted in all models and when the study sample was stratified by sex and origin, with all but those of Western origin showing a graded decrease with increasing age at migration categories. Conclusion: Immigrants arriving earlier in childhood lose their protection against hypertension at adolescence relative to the Israeli-born, likely because of lifestyle acculturation. Prevention programs are needed, beginning upon arrival and placing emphasis on nutritional and physical activity habits. Abstract : Supplemental Digital Content is available in the text